2007
DOI: 10.1055/s-2007-961807
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Hormones in Human Skin

Abstract: Androgens and skin & Androgens relevant to the skin Among the circulating androgens, dehydroepiandrosterone (DHEA) and DHEA sulfate (DHEA-S) are predominantly produced in the adrenal cortex. Androstenedione is produced approximately equally by the adrenal cortex and the ovaries, and somewhat less by the testes [4]. These are weak prohormones that act only after conversion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
232
1
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(265 citation statements)
references
References 173 publications
5
232
1
15
Order By: Relevance
“…This study is not only consistent with previous work describing human skin as both a hormone target and an endocrine gland (20)(21)(22)40), but establishes that early passage (P3) primary cultures of human dermal fibroblasts and epidermal keratinocytes retain in culture the key steroidogenic proteins seen in whole skin biopsies that are required for the conversion of cholesterol to potent androgens and estrogens (Fig. 1).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study is not only consistent with previous work describing human skin as both a hormone target and an endocrine gland (20)(21)(22)40), but establishes that early passage (P3) primary cultures of human dermal fibroblasts and epidermal keratinocytes retain in culture the key steroidogenic proteins seen in whole skin biopsies that are required for the conversion of cholesterol to potent androgens and estrogens (Fig. 1).…”
Section: Discussionsupporting
confidence: 79%
“…However, the complex pathways of steroid intracrinology and regulation of receptor expression in human skin are still poorly understood. Although the presence of AR, ERa, and ERb in human skin is well established (11,(19)(20)(21)(22), there is increasing evidence that rapid, nongenomic estrogen signaling is mediated by GPR30, also known as GPER1 (23)(24)(25), yet its expression in adult human skin has not been reported. The first aim of this study was to determine whether early passage (P3) primary cultures of human skin dermal fibroblasts and epidermal keratinocytes, the key mesenchymal and epithelial cells in the skin, retain the vital steroidogenic machinery required for the conversion of cholesterol to potent androgens and estrogens and therefore would be relevant in vitro models for functional studies of steroid hormone action.…”
mentioning
confidence: 99%
“…HF immune privilege, connective tissue sheath (CTS) mast cell degranulation. (see Arck et al, 2005a; Bodó et al, 2005 and2007; Botchkarev et al, 2004; Colombe et al., 2007; Deplewski and Rosenfield, 2000;Hasse et al, 2007; Kauser et al, 2006;Ohnemus et al, 2006;Paus et al, 2006;Peters et al, 2006b and2007;Philp et al, 2004;Slominski et al, 2007;Telek et al, 2007;Zouboulis et al, 2007) While this remains to be conclusively demonstrated, it is likely that HFeSC are fully integrated into this neuroendocrine tapestry of general HF biology. However, all we have to go by currently are some pointers to potentially important elements in the as yet obscure neuroendocrinology of HFeSC.…”
Section: Page 4 Of 38mentioning
confidence: 99%
“…Androgens have long been known to play a key role in the development of acne [76,77], seborrhoea [75], hirsutism, and androgenic alopecia [78].…”
Section: The Role Of Androgen Biosynthesis Genes In the Pathogenesis mentioning
confidence: 99%
“…The pilosebaceous unit, an endocrine organ, is an important source of localized hormone production, but also a target of various hormones synthesized elsewhere in the human body [75].…”
Section: Polymorphisms Of Genes Playing a Role In The Steroid Hormonementioning
confidence: 99%